2018
DOI: 10.2166/washdev.2018.049
|View full text |Cite
|
Sign up to set email alerts
|

Developing a water quality index in a tropical reservoir using a measure of multiparameters

Abstract: A water quality index (WQI) for the Adolfo López Mateos Dam (ALMD) was developed based on statistical multiparameter tools assisted with linear programming. ALMD was selected due to its social and economic significance in Sinaloa, the state with the highest agricultural production in Mexico. Twenty-six water-quality parameters were analyzed for four sampling points distributed along the dam during 2012–2017. The data were analyzed using Pearson's correlation matrix, principal components analysis (PCA) and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The nutrient loadings produce chemical and biological changes in water bodies and have a direct and detrimental effect on water quality [ 30 ]. Total nitrogen was found in concentrations ranging from 0.115 to 1.441, with a mean value of 0.67 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrient loadings produce chemical and biological changes in water bodies and have a direct and detrimental effect on water quality [ 30 ]. Total nitrogen was found in concentrations ranging from 0.115 to 1.441, with a mean value of 0.67 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in the Adolfo Lopez Mateos (ALM) reservoir is reported by Quevedo-Castro et al [ 30 ] who implemented a water quality index (WQI). Using multiparametric statistical tools, they analyzed 26 water quality parameters obtained from the year 2012-2017.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant vegetation is tropical deciduous forest, with small areas of pine-oak and pine forests toward the northwestern part [26]. Since high productivity is observed in the basin, a large proportion of the land is intended for agricultural and livestock activities [31].…”
Section: Methodsmentioning
confidence: 99%
“…The ALM reservoir (Culiacan, Mexico) is in the Humaya River basin (25°05′25″, 25°20′15″ North, 107°33′00″, 107°15′00″ West) at 186.5 m above the sea level (m.a.s.l.). The ALM dam is 105.5 m high, and 765 m long, considered one of the main sources of water for agricultural irrigation, power generation, fishing, and tourist activities [26][27][28], covering 11,354 ha and ranked tenth in Mexico according to its storage capacity [29] (Figure 1). The Humaya River basin is characterized by a warm humid climate toward the center and south, with summer rains.…”
Section: Study Areamentioning
confidence: 99%
“…This Pearson correlation analysis was used to separately describe the impact of each water quality parameter and to study the relationship (or correlation) between the quantitative variables (Quevedo-Castro et al 2018; 2019). The purpose of the principal component analysis was to obtain a reduced number of linear combinations of the water quality parameters which easily explain the variability of the data(Liu et al 2021;Quevedo-Castro et al 2018;Wisitthammasri et al 2020…”
mentioning
confidence: 99%